2017
DOI: 10.1097/md.0000000000008243
|View full text |Cite|
|
Sign up to set email alerts
|

Clinical characteristics and prognostic risk factors of healthcare-associated pneumonia in a Korean tertiary teaching hospital

Abstract: The 2016 American Thoracic Society and Infectious Diseases Society of America (ATS/IDSA) guidelines removed the concept of healthcare-associated pneumonia (HCAP). We examined whether the 2016 ATS/IDSA guidelines are applicable in Korea.We conducted a retrospective, observational study of pneumonia patients who were hospitalized at a tertiary teaching hospital from March 2012 to February 2014. Identified pathogens that were not susceptible to β-lactams, macrolides, and fluoroquinolones were defined as community… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
10
2

Year Published

2017
2017
2021
2021

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 15 publications
(17 citation statements)
references
References 22 publications
2
10
2
Order By: Relevance
“…Older age, ICU, and tracheal cannula were associated with higher mortality due to HAP, which is consistent with the finding of previous studies [ 15 17 ]. Although the CPIS has shown a low diagnostic performance in recent studies [ 18 , 19 ], CPIS ≥7 was a risk factor for mortality due to HAP in our study.…”
Section: Discussionsupporting
confidence: 92%
“…Older age, ICU, and tracheal cannula were associated with higher mortality due to HAP, which is consistent with the finding of previous studies [ 15 17 ]. Although the CPIS has shown a low diagnostic performance in recent studies [ 18 , 19 ], CPIS ≥7 was a risk factor for mortality due to HAP in our study.…”
Section: Discussionsupporting
confidence: 92%
“…As reported previously 10 , identified pathogens that were not susceptible to β-lactams, macrolides, and fluoroquinolones were defined as multidrug-resistant (MDR) pathogens.…”
Section: Methodsmentioning
confidence: 99%
“…One clinical report from an Asian tertiary teaching hospital showed that Klebsiella spp. and Streptococcus pneumoniae are two leading pathogens of healthcare-associated pneumonia (6). It has been reported that patients with K. pneumoniae chest infection frequently suffer a rapid, fatal outcome (7), and physicians should understand the clinical characteristics of Klebsiella chest infections; however, there have been no recent reports investigating how chest infections due to Klebsiella spp.…”
Section: Introductionmentioning
confidence: 99%